Research qualitatively: meanings since the work of the degree UPEL-IPB masters (Gaceta Técnica, 2015)
The article reports a research that was aimed to interpret the social meanings that emerge in doing qualitative research in the works of the masters of UPEL - IPB. It focuses on the qualitative paradigm approach, based on the hermeneutic phenomenological method, with the versionists two recent graduates participants and four participants in performing the work of master’s degree UPEL IPB, who underwent in-depth interviews; and the respective analysis coding and categorization was used. The role of tutor, researcher reflexivity, difficulties in the process, new relationship of social actors, personal growth and importance of the experience: Among the findings were unveiled five guiding categories
Keywords: qualitative research; undergraduate work; learning of research